AVIATION AND SPACE INDUSTRY OF UKRAINE: TECHNOLOGICAL AND LEGAL PROSPECTS OF DEVELOPMENT - Lykhova, Sofiia; Bilenchuk, Petro; Obikhod, Tetiana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: the history of the emergence and development of the aviation and space industries in Ukraine is considered for the sake of a deeper understanding of their current state and the formulation of well-founded recommendations regarding development prospects. Methods: the method of historical analysis was used to outline the prerequisites for the formation and development of the air and space industries in Ukraine, their legal component was analyzed using the methods of analysis and synthesis, and the relationship between the goals, functions, and future technologies of these industries was determined. Results: the problem of the formation and development of the modern air and space industries in Ukraine was updated, the need for the development and use of future technologies in the aviation industry was updated, the historical and legal aspects of both international space law and space law in Ukraine were outlined; the need for environmental safety in the conditions of the development of space activities is emphasized; the question of the need to regulate private space initiatives was raised. Discussion: components of a comprehensive approach to the future development of the aviation and space industries in Ukraine, the need for prompt regulation of the legal component of space and air activities in international law and the law of Ukraine, the formation of a creative approach to this industry in the conditions of rapid development of scientific, technological and political components in the civilized world . The development of the aviation and space industries, taking into account the needs of practical activities and the current level of scientific and technological development, has a positive effect on the nature of aviation and space-legal relations and the organization of almost all types of activities for the exploration and use of air and outer space. The implementation of current tasks is impossible without a modern regulatory framework, strengthening safety and supervision rules, improving airspace management, eliminating environmental impact, and harmonizing with international aviation standards. Commercialization of space activities requires the theoretical development of issues of responsibility in the space industry, which leads to the need for legal regulation of the use of outer space at the level of national legislation.